Immune checkpoint inhibitors for unresectable or metastatic pleomorphic dermal sarcomas - Helbig, Doris; Klein, Sebastian (Frontiers in Oncology, 2022)
Pleomorphic dermal sarcomas (PDS) are rare neoplasms of the skin that occur in UV-exposed sites in the elderly, but represent the most common cutaneous sarcomas. Although the majority of PDS can be surgically removed, local recurrences occur in up to 28%, usually occurring within the first two years after primary excision. Metastases are diagnosed in up to 20% of cases, mainly observed in the skin, lymph nodes and lungs, preferentially affecting patients with underlying hemato-oncologic diseases. Similar to other UV-induced tumors, PDS are inflammatory and immunogenic tumors (with a high number of CD4+/CD8+ tumor-infiltrating lymphocytes (TILs) and checkpoint molecule expression such as PD-L1, LAG-3, TIGIT) with a very high mutational burden. The most common genetic alterations include UV-induced TP53 loss of function mutations, followed by alterations in the CDKN2A/B gene. Rarely, targetable genetic alterations can be detected. Compelling experimental data and clinical reports about PD-1/PD-L1-blocking antibodies in patients with PDS suggest its use as first line treatment in unresectable or metastatic tumor stages. However, individual („off-line“) patient management should be discussed in an interdisciplinary tumor board based on molecular genetic testing, mutational burden, PD-L1 expression, and evidence of tumor-infiltrating lymphocytes in addition to comorbities of the individual patient.